Development of academic information system using webassembly technology - Lokapitasari Belluano, Poetri Lestari; Purnawansyah, Purnawansyah; Saiman, La; Panggabean, Benny Leonard Enrico (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
The Academic Information System (in Indonesian often abbreviated as SIAKAD) is a system developed to manage student data that aims at facilitating online academic administration activities. It aims to provide academic information services in the form of web applications, where teachers can independently create student academic reports to synchronize data into the DAPODIK system, a primary education data system, and develop academic information systems using web assembly according to user experience (UX) and developer experience (DX). The research method consists of field studies and literature related to web assembly, primary education data (DAPODIK), and the Academic Information System (SIAKAD). This information system and database were built using the Convention Over Configuration paradigm. The design phase used a prototyping model to graphically represent the system workflow and used an experimental research approach. Moreover, the study used an integrated modeling language (UML), and a Database Management System using PostgreSQL, and alpha testing for model testing. The Client Application was built using the C# programming language for users to generate student academic reports every semester. Processing data transactions using web assembly took less time than the traditional web, which was less than 300 milliseconds.